An ontological approach to represent knowledge in territorial planning science - Cataldo, Antonia; Rinaldi, Antonio M. (Computers, environment and urban systems, 2010)
Territorial planning science pertains to the governance of land transformations. Therefore it concerns several matters and heterogeneous subjects that use knowledge as a basis. Formal methodologies and techniques of knowledge representation are fundamental tools for the governance of land transformations and for sharing information among involved subjects. We propose and implement an ontology-based model of knowledge in the framework of landscape planning, with a particular emphasis on cultural landscape, to resolve conceptual misunderstandings and semantic ambiguities, and to provide a precise and accurate description of the current state of our knowledge.